Effects of Acetamiprid and Flupyradifurone-Based Insecticides on Soil Fauna: Research on Nematodes and Earthworms - Stefanovska Tatyana; Skwiercz Andrzej Tomasz; Zhukov Olexander; Husieva Anastasiia (Journal of Horticultural Research, 2025)
The extensive use of neonicotinoid and butenolide insecticides in horticultural systems has raised concerns about their potential effects on nontarget soil organisms, including plant-parasitic nematodes and earthworms. This study evaluates the effects of two commonly used insecticides, a neonicotinoid (acetamiprid) and butenolide (flupyradifurone), on the survival of plant pathogenic nematodes Hirschmanniella baltica, Ditylenchus laurae, and the earthworm Eisenia fetida in horticultural soils. A four-parameter Weibull model was used to analyze the survival dynamics following exposure of nematodes to one concentration of acetamiprid and Eisenia fetida to two concentrations. Both insecticides exhibited similar toxicity to earthworms, emphasizing the need for careful consideration of their use in sustainable pest management practices. These findings highlight the importance of evaluating the ecological risks of insecticides in horticulture, particularly regarding their unintended consequences on soil fauna. Further research is recommended to optimize the use of these insecticides while minimizing potential harm to beneficial soil organisms.